On the Cultural Genealogy of the Method in Dau: Ideology, Aesthetics, Ethics - Chukhrov, Keti (Stasis, 2023)
Unlike numerous critical texts that question the ethical and institutional characteristics of Ilya Khrzhanovsky’s Dau project, in this paper I explore the project’s genesis as a cultural and ideological phenomenon. I reveal the project’s bonds with its cultural predecessors, such as Anatoly Vasiliev, Boris Yukhananov, Yuri Mamleev, Vladimir Martynov, and Vladimir Sorokin. I research not only the study of Soviet totalitarianism in Dau (which the project meticulously reenacts) but also the genealogy of dissident and postsocialist non-conformist cultural codes, which, despite their critique of totalitarianism, often fall into the trap of reproducing those totalitarian features. Mapping artistic devices used in Dau, the paper then focuses at length on the issues of power distribution in the organization of performative process enacted by the project’s participants.